HUBUNGAN ASUPAN ENERGI DAN ZAT GIZI MAKRO DENGAN STATUS GIZI SANTRI PUTRI DI PONDOK PESANTREN SALAFIYAH AL-JAWAHIR - Nurlabibah, Najia; Hapsari, Agustina Indri; Rosmana, Dadang; Hastuti, Widi (Jurnal Gizi dan Dietetik, 2023)
Undernutrition or overnutrition is a health problem that is often found in adolescents. In Islamic boarding schools, intake is not given enough attention because of the large number of students. Intake of nutrients can affect nutritional status. The purpose of this study was to determine the relationship between energy intake and macronutrients (carbohydrates, fat, and protein) with the nutritional status of female santri at Pondok Pesantren Salafiyah Al-Jawahir. The research design used was cross sectional with proportional random sampling technique being used as a sample. Retrieval of food intake data using the SQ-FFQ method. Nutritional status is obtained from BMI/U parameters. The sample used was 54 people. The results showed that there was no significant relationship between energy intake and nutritional status (p=0.140), there was no significant relationship between protein intake and nutritional status (p=0.120), there was no significant relationship between fat intake and nutritional status (p = 0.087), and there was no significant relationship between carbohydrate intake and nutritional status (p = 0.303). It is suggested to the students of Al-Jawahir Salafiyah Islamic Boarding School to pay more attention to nutrition and increase food portions because adolescence is a period of growth.